1921
DOI: 10.1037/h0093140
|View full text |Cite
|
Sign up to set email alerts
|

Leading and legibility.

Abstract: In the literate adult, reading is a rapid, smooth-running, and highly automatized performance, which may go on for a long time without noteworthy lapse or hesitation. It appears to be a simple operation, but it is not. Even in highly practiced subjects it can scarcely be called "simple," because it depends upon the cooperation of a large number of heterogeneous conditions. In the first place, the constant readjustment of the eyes to the page is complicated. The leaps and pauses which the eyes make in reading i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, very large interline spacing may be no better, because it may increase the difficulty of tracking from line to line, thus increasing fixation times and reducing reading speed. The preceding discussion suggests a possible inverted-U-shaped relationship between interline spacing and legibility that finds empirical support in research by Bentley (1921).…”
Section: Typographic Dimensions and Typographic Outcomesmentioning
confidence: 85%
“…However, very large interline spacing may be no better, because it may increase the difficulty of tracking from line to line, thus increasing fixation times and reducing reading speed. The preceding discussion suggests a possible inverted-U-shaped relationship between interline spacing and legibility that finds empirical support in research by Bentley (1921).…”
Section: Typographic Dimensions and Typographic Outcomesmentioning
confidence: 85%
“…This is consistent with some reports that crowding is a near-resolution phenomenon. 15 By varying the amount of leading between lines of text, Bentley 18 and Paterson and Tinker 19 found that reading speed improved with a leading of between 2 and 8 points. Tinker reported a "safety zone" (the limits within which satisfactory legibility is assured) of between 1 and 4 points of leading for a variety of print sizes and line lengths.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a handful of previous studies have provided some insight into this issue. The earliest studies that are relevant to the issue of word spacing and reading speed are probably those of Bentley 18 and Paterson and Tinker, 19 who examined the effect of line spacing (also known as leading in typography) on reading speed. In both studies, a fixed character size was used (10-or 12-point size), and line spacing was manipulated by adding between 1 and 9 points to the "set solid" condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So, in the present study we used Times New Roman Font for estimating maximum reading speed of subject. Bentley 10 , Peterson and Tinker 11 , examined the effect of line spacing on reading speed and concluded thatincreased vertical word spacing, benefits reading speed.Similar result is obtained in present study but up to a spacing of 3x Calabrese A. et.al. 15 concluded that increasing interline spacing is advisable only for very slow readers (<20 words/min) who want to read a few words (spot reading).…”
Section: Resultsmentioning
confidence: 99%